Brain metastasis from renal urothelial carcinoma successfully treated by metastasectomy - Wen-Kuei Fang; Yeong-Chin Jou; Yuan-Chang Dai; Pi-Chan Ko; Ya-Fang Huang (Tzu Chi Medical Journal)
Upper tract urothelial cancer (UTUC) arises from the urothelial lining of the urinary tract. UTUC spreads in several different ways including direct invasion, lymphatic spread, and hematogeneous metastases. Regional lymph nodes are commonly the initial site of metastasis, followed by the liver, lung, and bone. Brain metastasis is uncommon in patients with urothelial carcinoma. Here, we report an uncommon case of kidney urothelial carcinoma with brain metastasis in a 55-year-old woman presenting with dysarthria with right side limb weakness. The patient recovered well after resection of the brain lesion without any sequelae after 1 year of follow-up.